ANALISIS LEVERAGE TERHADAP KEMAMPULABAAN DAN NILAI PERUSAHAAN - Hidayat, Lukman; Desury, Dita (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
Leverage is the use of sources of equity funds (equity) or in other words the company uses debt as a result of the use of the debt which will appear as fixed costs borne by the company and profitability is an indicator of how well a company generate profits or gains, while the value of the company refers to the level of confidence society to a company. The purpose of this study was to determine the influence and leverage relationships (X) to profitability (Y1) and Value (Y2) which is engaged in coal mining, namely PT Tambang Bukit Asam Tbk, PT Bumi Resources, Tbk, and PT ATPK Resources, Tbk the study period from 2003 to 2012. Leverage that I use is the Degree of Operating Leverage (DOL), while for the profitability using retum on equity (ROE) and value the company using the Price Earnings Ratio (PER). The analytical method used is the ratio analysis method and test through SPSS 20.0 is correlation, coeficient of determination and regression coeficients. The results of this study are, leverage has a significant connection to the profitability of 0.005 or 5%, while leverage on firm value has no significant relationship was 0.290 or 29.0%. Influence between leverage on profitability is stronger than the influence of leverage on finn value . Keywords: Leverage, profitability, Corporate Value